Barron's How to prepare for the SAT 2009 - Green, Sharon Weiner (Trẻ, 2008)
No other book offers you as much. Your personal tutor embodies Barron’s ongoing commitment to provide you with the best possibel coaching for the SAT and every other important test you take. It has benefited from the dedicated labors of Linde Turner and other members of the editorial staff of Barron’s all of whom wish you the best as you settle down with your tutor to work on the SAT